Stress reactivity links childhood trauma exposure to an admixture of depressive, anxiety, and psychosis symptoms. (February 2018) - van Nierop, Martine; Lecei, Aleksandra; Myin-Germeys, Inez; Collip, Dina; Viechtbauer, Wolfgang; Jacobs, Nele; Derom, Catherine; Thiery, Evert; van Os, Jim; van Winkel, Ruud
Abstract: Childhood trauma exposure has been associated with a clinically relevant mixed phenotype of psychopathology composed of depressive, anxiety, and psychosis symptoms, across healthy and clinical samples. Altered stress-reactivity after exposure to childhood trauma may be a plausible underlying mechanism explaining this association. In a general population sample of female twins (T0 = 564; T1 = 483), associations between childhood trauma exposure and symptom profile (no symptoms, isolated symptoms, or a mixed phenotype) on the one hand, and daily life stress reactivity on the other were investigated. Daily life stress reactivity was measured using the Experience Sampling Method (ESM), and was defined as negative affect reactivity to minor daily life stressors. Individuals exposed to childhood trauma who reported a mixed phenotype of psychopathology showed a significant increase in emotional reactivity to daily life stress (activity and social stress), compared with trauma-exposed individuals without a mixed phenotype. In the trauma-exposed mixed phenotype group, increased emotional reactivity to event-stress predicted more severe symptoms at ± 14 month follow-up. This study found evidence that may link heightened emotional reactivity to stress in individuals with a trauma history to the risk for later comorbid psychopathology. Highlights: Emotional daily life stress reactivity links childhood trauma to the development of an admixture of depressive, anxiety, and psychosis symptoms. Individuals with a CT history and mixedphenotype reported more emotional reactivity to daily life stress. Individuals with aCT-history and increased emotional reactivity to stress may be at risk forlater comorbid psychopathology.